Evaluasi dan Perbaikan Desain Antarmuka Pengguna Sistem Informasi Manajemen Pelaporan Sarana dan Prasarana Fakultas Ilmu Komputer Universitas Brawijaya Menggunakan Pendekatan Human-Centered Design (HCD) - Kadek Saka Andrika Putra; Ismiarta Aknuranda; Satrio Agung Wicaksono (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Sistem Informasi Manajemen Pelaporan Sarana dan Prasarana (Simasprana) is an Android application to report complaints regarding infrastructures in Faculty of Computer Science (Filkom) University of Brawijaya (UB). The application can be used for all academic community in Filkom UB. In previous development, it did not include user involvement especially in the user interface development. It is necessary to include the participation of users in the development of the user interface in the hope of getting feedback from users. This study aims to make design recommendations based on users requirements with the objective of making improvements to the user interface design. In addition, this study will also comparing usability scores of the previous design and the design recommendations. In the process of making user interface recommendations, Human Centered Design (HCD) approach is used and to obtain usability scores, usability testing is carried. The tests is conducted on six participants. Participants were asked to run several task scenarios and fill out the Post Study System Usability Questionnaire (PSSUQ) questionnaire to measure satisfaction levels. Interactive prototypes were made as the design recommendations. The test results on design recommendations show increases in the scores of usability. On the aspect of effectiveness, the result of the success rate increased by 19.1%. On the efficiency aspect, the time-based efficiency (TBE) increased by 0.054 goals/sec and the overall relative efficiency increased by 50.6%. In the aspect of satisfaction, the result increased by 41.2%.